The post-common-envelope binary central star of the planetary nebula Ou 5: a doubly eclipsing post-red-giant-branch system. Issue 2 (23rd December 2021) - Jones, David; Munday, James; Corradi, Romano L M; Rodríguez-Gil, Pablo; Boffin, Henri M J; Zak, Jiri; Sowicka, Paulina; Parsons, Steven G; Dhillon, Vik S; Littlefair, S P; Marsh, T R; Reindl, Nicole; et al.
ABSTRACT: We present a detailed study of the stellar and orbital parameters of the post-common envelope binary central star of the planetary nebula Ou 5. Low-resolution spectra obtained during the primary eclipse – to our knowledge the first isolated spectra of the companion to a post-common-envelope planetary nebula central star – were compared to catalogue spectra, indicating that the companion star is a late K- or early M-type dwarf. Simultaneous modelling of multiband photometry and time-resolved radial velocity measurements was then used to independently determine the parameters of both stars as well as the orbital period and inclination. The modelling indicates that the companion star is low mass (∼0.25 M⊙ ) and has a radius significantly larger than would be expected for its mass. Furthermore, the effective temperature and surface gravity of nebular progenitor, as derived by the modelling, do not lie on single-star post-AGB evolutionary tracks, instead being more consistent with a post-RGB evolution. However, an accurate determination of the component masses is challenging. This is principally due to the uncertainty on the locus of the spectral lines generated by the irradiation of the companion's atmosphere by the hot primary (used to derive companion star's radial velocities), as well as the lack of radial velocities of the primary.